Synthesis and in vitro characterization of entirely S-protected thiolated pectin for drug delivery - Hintzen, Fabian (Eur J Pharm Biopharm, 2013)
The study was aimed to synthesize a thiolated polymer (thiomer) that is resistant to oxidation in solutions above pH 5. In order to protect a pectin-cysteine conjugate against premature oxidation, the thiomer was S-protected by a disulfide connected leaving group. Therefore, 2-mercaptonicotinic acid was first coupled to L-cysteine by a disulfide exchange reaction and the purified product was subsequently attached to pectin by a carbodiimide mediated amid bond formation. The obtained fully S-protected thiolated pectin was in vitro characterized with respect to co- and mucoadhesive properties and stability towards oxidation. The results indicated a 1.8-fold and 2.3-fold enhanced disintegration time at pH 6.8 of the S-protected thiolated pectin (Pec-Cys-MNA) compared to thiolated pectin (Pec-Cys) and unmodified pectin (Pec). Moreover, rheological measurements of polymer/mucus mixtures showed a 1.6-fold (compared to Pec-Cys) and 6.7-fold (compared to Pec) increased dynamic viscosity of Pec-Cys-MNA. On the other hand, in the presence of a strong oxidizing agent such as H(2)O(2)(0.3% v/v), no increase in viscosity of Pec-Cys-MNA could be observed. A 6-month experiment also demonstrated the long-term stability of a liquid formulation based on Pec-Cys-MNA. Further investigations proved that the first time all thiol groups on a thiolated polymer could be protected owing to the novel synthesis. Accordingly, these features may help to develop thiomer based liquid or gel formulations targeting mucosal surfaces such as nasal, ocular or vaginal drug delivery systems.